Toxicidade e atividade antitumoral do derivado acridínico (E)-1’-{(4-flúorbenzilideno)-amino}-5’oxo-1,5’diidro-10H-espiro[acridina9,2’-pirrol]-4’carbonitrila (AMTAC-07) - Batista, Tatianne Mota (2019)
Cancer is one of the leading causes of death in the world. It is now considered a human tragedy and its prevalence is steadily increasing. By 2018, cancer statistics in the United States predicted more than 1.7 million new cancers and more than 600,000 disease-related deathsAcridine derivatives are DNA intercalators and topoisomerase inhibitors, and thus the synthesis of novel acridine derivatives has been of interest in medicinal chemistry. The compound (E)-1'-{(4- fluorobenzylidene) amino}-5'oxo-1,5'-dihydro-10H-spiro [acridine-9,2'-pyrrole]- 4'carbonitrile (AMTAC-07) is an acridine derivative capable of inhibiting a topoisomerase II. However, despite data related to this mechanism of action, there are no reports in the literature describing the antitumor potential and toxicity profile of AMTAC-07. Thus, the present study aimed to evaluate non-clinical toxicity and antitumor activity in vivo and the possible antitumor mechanisms of action of AMTAC-07 in model of Ehrlich ascites carcinoma (CAE). In the non-clinical acute toxicity assay in mice, the administration of AMTAC-07 (2000 mg/kg), intraperitoneal (ip), did not cause death of the experimental animals, with the mean lethal dose (LD50) estimated to be greater than 5000 mg/kg. The use of the fish embryo toxicity test (FET test) indicated that the mean lethal concentration (LC50) of AMTAC-07 is greater than 36.8 μg/mL. For the evaluation of genotoxicity, the micronucleus test was performed in mice peripheral blood, and it was observed that AMTAC-07 (2000 mg/kg, i.p.) did not induce an increase in the number of micronucleated erythrocytes. In the CAE model, AMTAC-07 (12.5, 25 or 50 mg/kg, ip, seven consecutive days of treatment) was observed to reduce tumor volume and mass, cell viability, and total number of peritoneal tumor cells. It was observed that AMTAC-07 (50 mg/kg) did not induce cell cycle arrest. Microdensity of the vessels in the peritoneum of the animals was determined, being observed reduction of this parameter after treatment with AMTAC-07 (50 mg/kg) indicating antiangiogenic action. It was further observed that AMTAC-07 acts on the modulation of the tumor immune response by inducing increase in IL-1β, TNF-α, CCL2 and IL-4 cytokine levels. The fluorimetric assay using 2 ', 7'-diacetate dichlorofluorescein (DCFH-DA) allowed the observation that AMTAC-07 does not induce changes in the level of oxidative stress in the experimental model used. Regarding to toxicity, after antitumor treatment, it was observed that AMTAC-07 (50 mg/kg) did not induce significant changes in all parameters evaluated (metabolic, biochemical, hematological and histological parameters). The data presented, together, suggest that AMTAC-07 has low non-clinical toxicity and significant antitumor activity via antiangiogenic and immunomodulatory mechanisms.